A Case of Anencephaly with Concomitant Maternal Overweight: Clinical Presentation and Outcome - Ismirajna G.T, Kanesti; Panggung T.S, Sir; Nanda R.P, Gustie; Riana, Salsabila (Jurnal Health Sains, 2025)
Anencephaly, a lethal neural tube defect (NTD), results from failed cranial neural tube closure during early embryogenesis. Maternal risk factors, including obesity and inadequate periconceptional folic acid intake, are well-established contributors. This report describes a case involving a 29-year-old primigravida with a Body Mass Index (BMI) of 28.03 kg/m² (overweight) who was referred at 39 weeks gestation for delivery following a prenatal diagnosis of anencephaly. The patient had no personal history of chronic illness but had not taken folic acid supplements prior to conception, initiating prenatal vitamins only after pregnancy confirmation. A cesarean section delivered a male infant with classic features of anencephaly. Despite resuscitation, the newborn died shortly after birth. The development of anencephaly in this instance is associated with two key modifiable risk factors: maternal overweight status and the absence of preconceptional folic acid supplementation. Neural tube closure occurs within the first month of pregnancy, often before pregnancy recognition, making folic acid initiation after confirmation too late to prevent NTDs. Maternal overweight or obesity is an independent risk factor that can compromise the fetal environment and potentially alter folate metabolism. This case underscores the critical importance of preconception health counseling, emphasizing the necessity of folic acid supplementation for all women of reproductive age, commencing before conception. This public health measure is particularly crucial for women with elevated BMI.